2017
DOI: 10.1016/j.ijscr.2017.02.052
|View full text |Cite
|
Sign up to set email alerts
|

A case report of thoracic endometriosis – A rare cause of haemothorax

Abstract: HighlightsThe diagnosis of thoracic endometriosis is complicated, because it has no specific symptoms and signs, and often delayed. TES should be suspected in a reproductive age woman with exacerbating symptoms during the menstruation.TES treatment should be started with medicine. If medical therapy fails, surgical treatment should be performed.Our case report shows that TES may be the cause of dangerous situation when an urgent operation must be performed. It is the first case of TES that has required urgent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
2
23
0
1
Order By: Relevance
“…[2][3][4][5][6][7][8] These presentations result from the presence of endometrial tissue on the pleural surfaces (CCP, CPT, CPE, CPM), in the lung parenchyma (pulmonary nodule) or the airway (CHp). Pleural involvement is more common, accounting for about 83% of TES, while parenchymal and airway involvement account for 17%, [9] and our study found a similar distribution. An even rarer occurrence of endometriosis on the thoracic aorta has been reported.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8] These presentations result from the presence of endometrial tissue on the pleural surfaces (CCP, CPT, CPE, CPM), in the lung parenchyma (pulmonary nodule) or the airway (CHp). Pleural involvement is more common, accounting for about 83% of TES, while parenchymal and airway involvement account for 17%, [9] and our study found a similar distribution. An even rarer occurrence of endometriosis on the thoracic aorta has been reported.…”
Section: Discussionsupporting
confidence: 83%
“…[3,[5][6][7]9,10] It is an uncommon condition, documented in the literature mostly in case reports and case series. [5][6][7][9][10][11][12] An analysis of 110 case reports/series published in English was conducted by Joseph and Sahn in 1996, [13] and Channabasavaiah and Joseph, [4] in 2010, conducted a similar review with the same number of patients, covering a 6.5-year period. Haga et al, [14] in Tokyo, Japan, reported 84 cases of CPT while evaluating 570 cases of spontaneous pneumothorax in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical therapy consists of hormonal suppression of ovarian estrogen secretion that can be achieved with oral contraceptives, progesterone agonists, gonadotropin-releasing hormone agonists, and danazol. A combination of medical and surgical management is associated with low recurrence in a long-term follow-up [8,9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracic endometriosis syndrome (TES) is a rare disease in which a functioning endometrial tissue is observed in the pleura, lung parenchyma, airways, or diaphragm [1][2][3][4]. The clinical manifestations of thoracic endometriosis are catamenial pneumothorax (CP) [5], catamenial hemoptysis (CH), catamenial hemothorax (CHT) [6,7] and lung nodules [8]. Thoracic endometriosis dates back to as early as 1912 when the first case was documented [9].…”
Section: Introductionmentioning
confidence: 99%